Conventional and ohmic heating pasteurization of fresh and thawed sheep milk: Energy consumption and assessment of bacterial microbiota during refrigerated storage - Balthazar, Celso F.; Cabral, Lucélia [UNESP]; Guimarães, Jonas T.; Noronha, Melline F.; Cappato, Leandro P.; Cruz, Adriano G.; Sant'Ana, Anderson S. (Elsevier, 2022)
This study aimed to assess the energy consumption of ohmic heating (OH) and conventional heating (CH) for pasteurization of fresh and thawed sheep milk and their impact on bacterial microbiota throughout refrigerated shelf-life (4 °C ± 1, 15 days). OH pasteurization using 8.33 and 5.83 V/cm electric field strength spent 72–73% less energy than CH pasteurization (515 KJ). The cultivation-dependent approach showed that at least 4.2 log cycle reductions were achieved in sheep milk submitted to CH and OH pasteurization, regardless sheep milk was fresh or thawed. Data from amplicon sequencing indicated that Staphylococcus was the most prevalent genus in raw samples at day 1 (F1D1: 58.35%; T1D1: 69.50%), while Pseudomonas became the most abundant after 15 days under cold storage (F1D15: 50.15% and T1D15: 54.50%). The relative abundance of all bacterial genera assessed remained similar on pasteurized samples by CH and OH throughout refrigerated storage. Industrial relevance: Ohmic heating (OH) presents as a critical advantage rapid and uniform heating of fluid food material. No studies assessed the use of OH for pasteurization of sheep milk and to evaluate the impact of this technology on sheep milk bacterial microbiota during refrigerated storage. The findings of this study prove the feasibility of sheep milk pasteurization using OH8.33 V/cm. OH also ensured the bacteriological stability of sheep milk during 2 weeks of storage under refrigeration conditions prior to dairy products manufacturing. This approach comprises a cheaper and easier way to store milk when compared to frozen storage, with potential benefits to small farmers and dairy industries.
Keywords: Electricity; Emergent technologies; Food preservation; Shelf-life; Small ruminant; Thermal pasteurization